Identifying and validating the dimensions of service quality for the banking industry in Malaysia / Jasmine Vivienne Andrew - Andrew, Jasmine Vivienne (2010)
The strategic nature of the banking sector, being the life-blood of business and industry, has garnered considerable attention since the recent global financial crisis. The liberalization and deregulation of the financial sector that stimulated intense competition among banking institutions is an issue of concern. Excellent service quality is crucial to business survival in the present banking environment in order to gain competitive advantage and corporate profitability. Thus, it is essential to analyze the means of measuring and evaluating service quality provided by banking institutions as they adjust to the dynamic changes in the banking environment. Previous studies have produced scales that bear a resemblance to generic measures of service quality, which may not be totally adequate in assessing the perceived quality in the banking sector. This study aims to identify and validate the dimensions of service quality within the banking sector in Malaysia from the customers' perspective. A proposed 29-item instrument has been empirically tested for unidimensionality, reliability and validity using both exploratory and confirmatory factor analysis. A factorial analysis suggests that service quality has three dimensions namely 'Systemization of service delivery', 'Reliable Communication' and 'Responsiveness'. Systemization of service delivery relates to systematic and orderly arrangement of a bank's service delivery through effective, standardized and simplified procedures and process. The 'Responsiveness' factor describes the desire, willingness and readiness to assist customers and deliver prompt service, whilst 'Reliable Communication' emphasizes the necessity to communicate and perform the services in a dependable, reliable and understanding manner. A subsequent multiple regression analysis revealed that 'Systemization' is the most important service quality dimension within the banking sector.